Comparative structural analysis of Bru1 region homeologs in Saccharum spontaneum and S. officinarum. (December 2016) - Zhang, Jisen; Sharma, Anupma; Yu, Qingyi; Wang, Jianping; Li, Leiting; Zhu, Lin; Zhang, Xingtan; Chen, Youqiang; Ming, Ray
Abstract Background Sugarcane is a major sugar and biofuel crop, but genomic research and molecular breeding have lagged behind other major crops due to the complexity of auto-allopolyploid genomes. Sugarcane cultivars are frequently aneuploid with chromosome number ranging from 100 to 130, consisting of 70–80 % S. officinarum, 10–20 % S. spontaneum, and 10 % recombinants between these two species . Analysis of a genomic region in the progenitor autoploid genomes of sugarcane hybrid cultivars will reveal the nature and divergence of homologous chromosomes. Results To investigate the origin and evolution of haplotypes in theBru1 genomic regions in sugarcane cultivars, we identified two BAC clones fromS. spontaneum and four fromS. officinarum and compared to seven haplotype sequences from sugarcane hybrid R570. The results clarified the origin of seven homologous haplotypes in R570, four haplotypes originated fromS. officinarum, two fromS. spontaneum and one recombinant. . Retrotransposon insertions and sequences variations among the homologous haplotypes sequence divergence ranged from 18.2 % to 60.5 % with an average of 33.7 %. Gene content and gene structure were relatively well conserved among the homologous haplotypes. Exon splitting occurred in haplotypes of the hybrid genome but not in its progenitor genomes. Tajima's D analysis revealed thatS. spontaneum hapotypes in theBru1 genomic regions were under strong directional selection. Numerous inversions, deletions, insertions and translocations were found between haplotypes within each genome. Conclusions This is the first comparison among haplotypes of a modern sugarcane hybrid and its two progenitors. Tajima's D results emphasized the crucial role of this fungal disease resistance gene for enhancing the fitness of this species and indicating that the brown rust resistance gene in R570 is fromS. spontaneum . Species-specific InDel, sequences similarity and phylogenetic analysis of homologous genes can be used for identifying the origin ofS. spontaneum andS. officinarum haplotype inSaccharum hybrids. Comparison of exon splitting among the homologous haplotypes suggested that the genome rearrangements inSaccharum hybrids after hybridization. The combined minimum difference at 19.5 % among homologous chromosomes inS. officinarum would be sufficient for proper genome assembly of this autopolyploid genome. Retrotransposon insertions and sequences variations among the homologous haplotypes sequence divergence may allow sequencing and assembling the autopolyploidSaccharum genomes and the auto-allopolyploid hybrid genomes using whole genome shotgun sequencing.